An exploratory study to understand the mental health care needs of university students - Mudau, Tondani (University of the Witwatersrand, Johannesburg, 2023)
Background: Despite high levels of psychological distress, university students are reluctant to seek counselling on campus. University students have easy access to data and regularly use their phones for academic and personal purposes. A mental health application (app) designed specifically for university students has the potential to address mental health challenges and promote help-seeking amongst university students. This study aimed to explore the prevalence of psychological distress amongst university students, the sources of their distress and common coping strategies. The study then investigated students’ and counsellors’ perceptions of using a mental health app as a coping mechanism for psychological distress. Finally, the study developed, tested, and evaluated a mental health app specifically designed for university students. Methods: A multiphase mixed methods research design comprising three phases was used to collect quantitative and qualitative data through surveys, in-depth interviews, and focus group discussions. Data were collected, analysed and interpreted within the technology acceptance model (TAM) and cognitive behavioural theoretical frameworks. Phase 1 collected data to determine the prevalence of psychological distress, common coping strategies and mobile phone use amongst university students. Phase 2 integrated quantitative and qualitative data from Phase 1 to determine the feasibility of a mental health app, and thereafter developed the mental health app. Phase 3 tested and evaluated the usability of a mental health app with students and counsellors. All quantitative data were collected using the web-based application, Research Electronic Data Capture, and analysed using Statistical Analytics Software Enterprise Guide 7.1. All qualitative data were analysed through thematic analysis and by using NVivo version 12 Pro. Results: Overall, 1 221 students and nine counsellors were enrolled in the study. Phase 1 enrolled 1 100 students in an exploratory survey, 62 in focus group discussions, and six counsellors for in-depth interviews. Socio-demographic data Phase 1: A majority of participants (72.72%) were female, within the 18–20 age group (64.6%), and in their first-year level of study (46.2%). A vast majority (94.1%) were enrolled at the University of the Witwatersrand, with many enrolled in the faculty of humanities (36.1%). Most participants were South African citizens (95.6%) and from an urban location (61%), and 20.09% had been previously diagnosed with a mental health challenge. Prevalence of psychological distress: The Kessler-10 and student stress inventory were used to determine the prevalence of psychological distress. The results show that most participants (60.5%) reported very high levels of psychological distress, while 53% reported moderate levels of stress. Male students were more likely than female students to have very high levels of psychological distress (71.4%) and mild stress (63.3%). Third-year students were more likely than first- and second-year students to have high levels of psychological distress (65%) and moderate stress (59%). Coping strategies: The Brief-COPE-28 was used to determine common coping strategies amongst students. The results show that students with moderate or severe stress used emotion-focused (mean: 30.6 [SD = 5.71] vs 28.8 [SD = 6.21]; p < .0001) and avoidance coping styles (mean: 16.3 [SD = 3.82] vs 13.2 [SD = 3.51]; p < .0001) more than those with mild stress. A larger proportion of female than male students used denial (mean: 3.50 [SD = 1.77] vs 1.54 [SD = 3.13]; p = 0.001), emotional support (mean: 5.03 [SD = 1.96] vs 4.50 [SD = 1.82]; p = 0.0001), informational support (mean: 2.00 vs 1.88, p = 0.0001), behavioural disengagement, (mean: 3.63 [SD = 1.63] vs 3.82 [SD = 1.52]; p = 0.001), and religion (mean: 5.53 [2.24] vs 4.63 [2.17]; p = 0.001) as coping strategies. Students within the 18–20 age group had higher scores for religion as a coping strategy (mean: 5.53 [SD =2.2 2] vs 4.93 [SD = 2.23]; p = 0.0003). First-years were more likely to use problem-solving coping styles than postgraduate students (mean: 22.5 [SD = 5.86] vs 22.5 [SD = 5.29] p = 0.0165). Mobile phone use: Results from a sociodemographic questionnaire show that a majority of participants (98.7%) owned a smartphone and 66.9% owned a phone with Android software. Most (81%) reported having easy access to data and only a few (26.6%) had used an online health app for their health needs. Students’ and counsellors’ perceptions of psychological distress and using a mental health app to address mental health challenges: A semi-structured interview guide was used to collect qualitative data. Thematic analysis based on the TAM and cognitive behavioural theory frameworks categorised qualitative data under six main themes: (1) students’ conceptualisation of distress, (2) common mental health challenges, (3) perceptions of factors leading to distress, (4) facilitators of using a mental health app intervention, (5) barriers to using a mental health app intervention, and (6) perceived usefulness of the app. Sociodemographic data Phase 3: Three counsellors and 59 students were enrolled in the survey. Most students (64%) were female, within the 21–24 age group (63%), and in their third year of study (37%). More than half the student participants were enrolled at the University of the Witwatersrand (54%) and 29% within the humanities faculty. App testing: The app had eight categories for participants to test (information, coping strategies, take a test, seek help, journal, podcasts, videos, and settings). A majority of participants assessed coping strategies (73%) and information (69%), followed by the seek help (47%) and take a test (45%) category. Podcasts (23%) and settings (15%) were the least assessed categories. Perceived ease of use: The belief that users will require minimal effort using the technology was assessed using the Mobile Application Rating Scale (MARS). The overall MARS score showed excellent internal consistency (Cronbach alpha = 0.93) and was highly correlated to the app’s overall star rating (r = 0.72, p < 0.0001). The overall mean for the total MARS scale was 88.1. The MARS subscales were high quality and exceeded the (3.0) mean threshold: engagement (3.84), functionality (3.52), aesthetics (4.25), information (4.36), and subjective quality (3.45). Conclusion: The findings reveal that psychological distress is prevalent amongst university students, suggesting a need for student-friendly mental health interventions. A mental health app has the potential to address this need. This study found that most students own smart mobile phones and have easy access to data, indicating that a mental health app is a viable intervention. The qualitative findings demonstrate students’ willingness to use a mental health app for psychological distress. Barriers to using the app included a lack of face-to-face therapy, over-reliance on the app, fear of misdiagnosis, and lack of accessibility and affordability. Facilitators to using the app included previous experience with apps, convenience, accessibility, and confidentiality. These aspects were considered when designing the app, for it to be student friendly. Students and counsellors suggested that, for the app to be useful, it should provide information and coping strategies, offer support, engagement, and security. Therefore, the mental health app intervention in this study was developed based on these characteristics. The designed mental health app was evaluated by students and counsellors, who rated the app to be of high quality and easy to use. This outcome is positive and should be explored further. Future studies can longitudinally test for the app’s effectiveness with students experiencing psychological distress.
A research report submitted A thesis submitted for the degree of Doctor of Philosophy to the Faculty of Humanities, Department of Psychology, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023.
Keywords: mHealth; Digital Interventions; Mental Health; University Students; UCTD; SDG-3: Good health and well-being